2002
DOI: 10.1088/0951-7715/15/3/201
|View full text |Cite
|
Sign up to set email alerts
|

How to prune a horseshoe

Abstract: Let F : R 2 → R 2 be a homeomorphism. An open F-invariant subset U of R 2 is a pruning region for F if it is possible to deform F continuously to a homeomorphism F U for which every point of U is wandering, but which has the same dynamics as F outside of U. This concept is motivated by the Pruning Front Conjecture introduced by Cvitanović which claims that every Hénon map can be understood as a pruned horseshoe. This paper contains recent results on pruning theory, concentrating on prunings of the horseshoe. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 69 publications
0
8
0
Order By: Relevance
“…The dynamics of the DK flows appears to be reminiscent of the analysis of the dynamics of Lorenz attractors, as discussed for example in the survey by Ghys [18]. Moreover, the variation of the horseshoes for a smooth family for generic DK-flows with positive entropy suggests a comparison with the degeneration in the dynamics of the Lorenz attractors as studied by de Carvalho and Hall [9,10,11,19]. The analogy between the dynamics of a family of generic DK-flows and a family of Lorenz attractors suggests that the topic is worth further investigation.…”
Section: Derived From Kuperberg Flowsmentioning
confidence: 97%
“…The dynamics of the DK flows appears to be reminiscent of the analysis of the dynamics of Lorenz attractors, as discussed for example in the survey by Ghys [18]. Moreover, the variation of the horseshoes for a smooth family for generic DK-flows with positive entropy suggests a comparison with the degeneration in the dynamics of the Lorenz attractors as studied by de Carvalho and Hall [9,10,11,19]. The analogy between the dynamics of a family of generic DK-flows and a family of Lorenz attractors suggests that the topic is worth further investigation.…”
Section: Derived From Kuperberg Flowsmentioning
confidence: 97%
“…Clearly, the pruning front is expected to play a similar role as the critical point in the kneading theory. A mathematical formulation has been developed in [50,51].…”
Section: Pruning Of the Horseshoementioning
confidence: 99%
“…Then pruning family P(F ) is defined to be the closure, in the C 0 -topology, of the set of all the pruning homeomorphisms of F . It can be shown that P(F ) contains uncountably many different models of dynamics [8,9] and the PFC states that P(F ) contains enough models to describe all Hénon maps.…”
Section: Pruningmentioning
confidence: 99%